Paul Gilson Een Brusselse componist van de wereld - Bertels, Kurt (ASP editions - Academic and Scientific Publishers, 2023)
PAUL GILSON (1865-1942), born and raised in Brussels, grew into a valued artist during the fin de siècle. He was and is known as an erudite composer, orchestrator, theoretician, critic, musicographer and educator. A prestigious Prix de Rome (1889) and his symphonic work La Mer (1892) made him known far beyond the national borders. Because of his remarkable commitment to wind music, and that of amateur orchestras in particular, we still remember Gilson today as the Father of Belgian wind music. Gilson's extremely versatile artistry resonated with numerous international trends. He closely followed current musical life at home and abroad and reported extensively in newspapers, magazines and radio broadcasts. At the conservatories of Brussels and Antwerp and as a private teacher, he managed to stimulate and sustainably influence a new generation of composers and musicians. That pedagogical passion also challenged Gilson to bundle his sharp insights into theoretical tracts. All of these facets of Gilson's life and work are the focus of this book, with a particular focus on his national and international importance. From his life to his correspondence with Russians, from his elaborate theories to his music for wind orchestras, opera music and compositions for horn and saxophone: the authors of this volume provide an in-depth and extensive insight into the character of Paul Gilson.